Efektivitas Pemanfaatan Aplikasi LOCUS GIS dan MAPIT GIS Untuk Pengumpulan Data Pendaftaran Tanah - Muhammad Mahirda Ariwibowo; Suharno Suharno; Wahyuni Wahyuni (Tunas Agraria, 2020)
Abstract: The activity of collecting land registration data is the main stage in the Complete Systematic Land Registration program (PTSL). Nowadays, the acceleration strategy by utilizing information technology such as Locus GIS and Mapit GIS as an android-based application for support land data collection activities has been widely used, both free and paid. Therefore, the factors of effectiveness of the application are important to be considered by the users so that they can be used appropriately and optimally according to user needs. This study aims to explore important matters related to the features owned and their advantages and disadvantages and usability of applications for collecting land registration data. Mix methods were used in this study which combines two approaches, namely qualitative and quantitative approach. The data of this study was collected through interview, observation and questionnaire. The result of this study shows that 1) Application features of Locus GIS and Mapit GIS  can be used for land data collection by considering the advantages and disadvantages of each; 2) The results of evaluating the utility test toward both applications for land data collection in accordance with ISO / IEC 9126-1 and ISO / IEC 9126-4 standards shows that it is equivalent to "Good" in the ratings and "Very Effective" in the categories.Keyword: The Effectiveness, Locus GIS, Mapit GIS, PTSL. Intisari: Pengumpulan data pendaftaran tanah menjadi tahapan utama dalam program Pendaftaran Tanah Sistematis Lengkap (PTSL). Strategi percepatan dengan memanfaatkan teknologi informasi seperti Locus GIS dan Mapit GIS sebagai aplikasi berbasis android untuk mendukung kegiatan pengumpulan data pertanahan telah banyak digunakan dari yang gratis maupun yang berbayar. Maka dari itu faktor efektivitas aplikasi menjadi penting untuk dipertimbangkan pengguna sehingga bisa dimanfaatkan secara tepat dan optimal sesuai dengan kebutuhan pengguna. Penelitian ini bertujuan untuk mengeksplorasi hal penting terkait fitur yang dimiliki beserta kelebihan dan kekurangannya dan kedayagunaan aplikasi untuk pengumpulan data pendaftaran tanah. Penelitian dilakukan menggunakan mix methods yang menggabungkan dua bentuk pendekatan, yaitu kualitatif dan kuantitatif melalui wawancara, observasi dan pemberian kuesioner. Hasil penelitian ini 1) Fitur Aplikasi Locus GIS dan Mapit GIS dapat dimanfaatkan untuk pengumpulan data pertanahan dengan pertimbangan kelebihan dan kekurangan masing-masing; 2) Hasil evaluasi uji kedayagunaan kedua aplikasi untuk pengumpulan data pertanahan sesuai  standar ISO/IEC 9126-1 dan  ISO/IEC 9126-4 menunjukkan hasil dengan penilaian “Baik” dan kategori “Sangat Efektif”.Kata Kunci: Efektivitas, Locus GIS, Mapit GIS, PTSL.